Montagem e construção de um magnetômetro a efeito Kerr magneto-óptico - Gonçalves, Charlie Salvador (2006)
n this master s dissertation a Kerr Magneto Optic s magnetometer effect was set up to do characterization of samples type films fine and ultra thin, these samples will be grown after the implementation of the sputtering technique at the magnetism laboratory of of this department. In this work a cooled electromagnet was also built the water and that it reaches close values to 10kOe with a gap of 22 mm including an area of uniform field of 25mm of diameter. The first chapter treats of the construction of this electromagnet from its dimensioning to the operation tests that involve measures of reached maximum field and temperature of the reels when operated during one hour. The second chapter is dedicated to the revision of the magnetism and the magnetization processes as well as it presents a theoretical base regarding the magnetic energies found in films and magnetic multilayer. In the sequence, the third chapter, is especially dedicated the description of the effects magneto opticians the effect kerr in the longitudinal, traverse and polar configurations, using for so much only the classic approach of the electromagnetism and the coefficients of Fresnel. Distinguished the two areas of observation of the effect regarding thickness of the film. The constructive aspects of the experimental apparatus as well as the details of its operation are explained at the room surrender, also presenting the preliminary results of the measures made in one serializes of permalloy films and concluding with the results of the characterization of the first films of iron and permalloy grown here at the theoretical and experimental physics department at UFRN